PRMT3‐Mediated Arginine Methylation of METTL14 Promotes Malignant Progression and Treatment Resistance in Endometrial Carcinoma - Yiru Wang; Can Wang; Xue Guan; Ying Ma; Shijie Zhang; Fei Li; Yue Yin; Zhenxing Sun; Xiuwei Chen; Hang Yin (Advanced Science, 2023)
Abstract Protein arginine methyltransferase (PRMT) plays essential roles in tumor initiation and progression, but its underlying mechanisms in the treatment sensitivity of endometrial cancer (EC) remain unclear and warrant further investigation. Here, a comprehensive analysis of the Cancer Genome Atlas database and Clinical Proteomic Tumor Analysis Consortium database identifies that PRMT3 plays an important role in EC. Specifically, further experiments show that PRMT3 inhibition enhances the susceptibility of EC cells to ferroptosis. Mechanistically, PRMT3 interacts with Methyltransferase 14 (METTL14) and is involved in its arginine methylation. In addition, PRMT3 inhibition‐mediated METTL14 overexpression promotes methylation modification via an m6A‐YTHDF2‐dependent mechanism, reducing Glutathione peroxidase 4 (GPX4) mRNA stability, increasing lipid peroxidation levels, and accelerating ferroptosis. Notably, combined PRMT3 blockade and anti‐PD‐1 therapy display more potent antitumor effects by accelerating ferroptosis in cell‐derived xenograft models. The specific PRMT3 inhibitor SGC707 exerts the same immunotherapeutic sensitizing effect in a patient‐derived xenograft model. Notably, blocking PRMT3 improves tumor suppression in response to cisplatin and radiation therapy. Altogether, this work demonstrates that PRMT3 depletion is a promising target for EC.